Wanurejo Village Development Through Balkondes in Borobudur District Magelang Regency, Central Java - Amin Kiswantoro; Kiki Rizki Makiya; Rizky Maulana; Dwiyono Rudi Susanto; Nur Rohman (Ideas Publishing, 2023)
Wanurejo Village is one of the villages located in the Borobudur Temple area which is unique as a